Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

1. Solve for [tex]x[/tex]:

[tex]\[ x^2 + 5x - 6 = 0 \][/tex]


Sagot :

To solve the quadratic equation [tex]\( x^2 + 5x - 6 = 0 \)[/tex], we can follow these steps:

1. Identify the coefficients: The standard form of a quadratic equation is [tex]\( ax^2 + bx + c = 0 \)[/tex]. In this equation, [tex]\( a = 1 \)[/tex], [tex]\( b = 5 \)[/tex], and [tex]\( c = -6 \)[/tex].

2. Set up the equation: With the given coefficients, our quadratic equation is:
[tex]\[ x^2 + 5x - 6 = 0 \][/tex]

3. Solve the quadratic equation by factoring: We look for two numbers that multiply to [tex]\( ac \)[/tex] (where [tex]\( a = 1 \)[/tex] and [tex]\( c = -6 \)[/tex]) and add up to [tex]\( b = 5 \)[/tex]. In this case, we are looking for two numbers that multiply to [tex]\(-6\)[/tex] and add to [tex]\(5\)[/tex].

- Factors of [tex]\(-6\)[/tex] that add up to [tex]\(5\)[/tex] are [tex]\(6\)[/tex] and [tex]\(-1\)[/tex].

4. Rewrite the middle term using these factors:
[tex]\[ x^2 + 6x - x - 6 = 0 \][/tex]

5. Factor by grouping: Group the terms in pairs and factor out the common factors from each pair:
[tex]\[ (x^2 + 6x) + (-x - 6) = 0 \][/tex]
[tex]\[ x(x + 6) - 1(x + 6) = 0 \][/tex]

6. Factor out the common binomial factor:
[tex]\[ (x - 1)(x + 6) = 0 \][/tex]

7. Set each factor equal to zero and solve for [tex]\( x \)[/tex]:
[tex]\[ x - 1 = 0 \quad \text{or} \quad x + 6 = 0 \][/tex]
[tex]\[ x = 1 \quad \text{or} \quad x = -6 \][/tex]

So, the solutions to the equation [tex]\( x^2 + 5x - 6 = 0 \)[/tex] are [tex]\( \boxed{-6 \text{ and } 1} \)[/tex].